Perkembangan Sistem Pendidikan di Jerman - Syaza Sahira; Mislaini Mislaini; Widya Febriani (Universitas Palan, 2025)
The German education system is recognized as one of the best in the world, having rapidly developed after World War II through a structured and innovative approach. This system emphasizes decentralization, allowing educational policies to be tailored by each federal state, and focuses on fostering student independence, teacher quality, and equitable access to education. Germany has successfully nurtured a generation that excels not only academically but also in character and adaptability. This study explores the development of Germany's education system, from primary education to higher education, with an emphasis on its flexible curriculum model, government support for free education, and the integration of cultural values and moral education in character building. The findings offer insights into how Germany has utilized education as a fundamental asset for building an independent and globally competitive nation.